(untitled) (Journal of the College of Basic Education, 2022)
The aim of the current research is to know the effect of using the expert’s mantle strategy on the achievement of fifth-grade literary students in philosophy and psychology. The researcher conducted an experiment that lasted an entire semester, and an experimental design was chosen for the two equal groups (experimental and control), as the researcher chose Al-Makassed High School within the Tikrit district. The sample consisted of (50) students in two groups, the experimental were taught using the expert mantle strategy, and the control group was taught in the usual way. The researcher rewarded the two groups in (age in months and intelligence) - The scientific material for the research, represented by the second part of the book on philosophy and psychology scheduled for the academic year 2019 - 2020, has been identified, and the appropriate behavioral objectives have been formulated. - The researcher prepared a research tool where he used an achievement test, the results were processed statistically using descriptive statistical methods such as (measures of dispersion, central tendency and correlation coefficients), and inferential, including t-tests, as well as non-parametric statistical means such as chi-square, and the results revealed the preference of the experimental group over The control group in achievement, and the researcher concluded that the adoption of the strategy of the mantle of the expert in teaching has a positive impact on the achievement of the fifth grade literary students, and in light of this the researcher put forward a number of recommendations in addition to a number of proposals